Corporate Governance, Market Share, and Intellectual Capital Disclosure: Evidence from the Indonesian Agriculture and Mining Sectors - Hatane, Saarce Elsye; Kuanda, Elenne Stefanie; Cornelius, Elizabeth; Tarigan, Josua (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 1 (2020), 2020)
Using a sample of Indonesian agricultural and mining companies, this study aims to provide empirical evidence to prove the effects of auditor type, the board size, and audit committee on intellectual capital disclosure (ICD). The sample consisted of 18 agricultural and 28 mining companies, which were chosen using the content analysis method. The five-year observation period lasted from 2013 to 2017, resulting in 230 units of analysis. Data analysis employed a panel regression model with panel data testing. The study finds a positive impact of auditor type and audit committee on ICD as well as a negative influence of board size on ICD. The results conform to existing stakeholder and legitimacy theories. Keywords: Intellectual capital disclosure; auditor type; board size; audit committee